Penerapan Teknik Non-Linear Editing dalam Pembuatan Film Dokumenter “Apocalyptic Tides” - Yabes Yedija Wesley; Dimas Althalaric Mohammad Sultan; Toto Sugito; Aat Ruchiat Nugraha (BADAN PENERBIT STIEPARI PRESS, 2025)
The problem of waste dumping on Bali coast must be regarded as an ecological crisis which proves to be unseen under many perspectives. The article is about the making of a documentary film Apocalyptic Tides as an advocacy and educational tool bringing up this issue by means of the expository documentary style with highlights of poetry and performance elements in play. The method of field observation, semi-structured interviews with activist and scholars and visual documentation are also used in the research, followed by analysis and compiling of information with the help of non-linear editing tools by using Adobe Premiere Pro software. The film is set on a thematic narrative that shows the process of the waste as it goes upstream to downstream and how it affects the ecology and thoughts on the ecological consciousness. Techniques of non-linear editing were applied to organize the footage according to emotional echo and the schemes of meaning instead of the chronological order, thus creating an intellectually stimulating and reflective storyline. Apocalyptic Tides proves the power of documentary film to bridge the gap between art, science, and advocacy in case of creating the ecology-minded population.